Predicting psychotherapy outcome based on therapist interpersonal skills: A five-year longitudinal study of a therapist assessment protocol. (2nd November 2017) - Schöttke, Henning; Flückiger, Christoph; Goldberg, Simon B.; Eversmann, Julia; Lange, Julia
Abstract: Objective: In the past decade, variation in outcomes between therapists (i.e., therapist effects) have become increasingly recognized as an important factor in psychotherapy. Less is known, however, about what accounts for differences between therapists. The present study investigates the possibility that therapists' basic therapy-related interpersonal skills may impact outcomes. Method: To examine this, psychotherapy postgraduate trainees completed both an observer- and an expert-rated behavioral assessment: the Therapy-Related Interpersonal Behaviors (TRIB). TRIB scores were used to predict trainees' outcomes over the course of the subsequent five years. Results: Results indicate that trainees' with more positively rated interpersonal behaviors assessed in the observer-rated group format but not in a single expert-rated format showed superior outcomes over the five-year period. This effect remained controlling for therapist characteristics (therapist gender, theoretical orientation [cognitive behavioral or psychodynamic], amount of supervision, patient's order within therapist's caseload), and patient characteristics (patient age, gender, number of comorbid diagnoses, global severity, and personality disorder diagnosis). Conclusions: These findings underscore the importance of therapists' interpersonal skills as a predictor of outcome and source of therapist effects. The potential utility of assessing therapists' and therapists-in-training interpersonal skills are discussed.